Foot care knowledge and practices among Japanese nurses and care workers in home care and adult service center: a cross- sectional study - Kashiko Fujii; Takuyuki Komoda; Atsuko Maekawa; Mariko Nishikawa (BMC, 2020)
Abstract Background Foot care knowledge and practices among nurses and care workers in the community greatly impact foot health maintenance and prevention of foot-related problems among older people. This study aimed to explore and examine the current foot care knowledge, practices, and perceptions among nurses and care workers at home care and adult day service center, along with their demographic characteristics and daily care for clients. Methods This study analyzed 232 randomly selected front-line nurses and care workers working at home care or adult day service center in one of the selected cities, Aichi Prefecture, Japan. Data were obtained using questionnaires and subsequently analyzed using descriptive statistics, t-tests, Chi-square tests, Wilcoxon rank-sum tests, and Spearman's rank correlation tests. Results Among the 305 surveyed, 232 (62 nurses; 170 care workers) provided data. Although 57 nurses (91.9%) and 142 care workers (83.5%) showed interest in foot care, 33 nurses (53.2%) and 133 care workers (78.2%) stated that foot care education was insufficient. Knowledge and practice scores were associated with working status. Higher accuracy differences in the early detection of foot problems and skin tears on lower limbs in knowledge category were observed between nurses and care workers. The nurses as well as the care workers had low accuracy rates of knowledge questions regarding the use of shoes and socks subscale. For practice, both nurses and care workers had low mean scores for checking client's shoes (2.0/5.0 and 2.1/5.0, respectively), method for reducing ingrown nail pain (2.6/5.0 and 1.9/5.0, respectively), and opportunity for discussing foot care with others (2.7/5.0 and 2.2/5.0, respectively). A significant correlation between knowledge and practice scores was observed among nurses (0.331, p < 0.05) and care workers (0.339, p < 0.001). Conclusions Despite the presence of several barriers toward enhanced care delivery to clients needing it most, nurses and care workers clearly understood the importance of foot care. These findings indicate that foot care should be focused by nurses and care workers to improve the knowledge and practice of foot care and to suggest future implications that efficient and understandable tools are needed considering their current working situation.